2022
DOI: 10.3389/fmicb.2022.959043
|View full text |Cite
|
Sign up to set email alerts
|

Generation of miniploid cells and improved natural transformation procedure for a model cyanobacterium Synechococcus elongatus PCC 7942

Abstract: The biotechnologically important and naturally transformable cyanobacterium, Synechococcus elongatus PCC 7942, possesses multiple genome copies irrespective of its growth rate or condition. Hence, segregating mutations across all genome copies typically takes several weeks. In this study, Synechococcus 7942 cultivation on a solid growth medium was optimised using different concentrations of agar, the addition of antioxidants, and overexpression of the catalase gene to facilitate the rapid acquisition of coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Even those relatively simple organisms lack reliable genetic modules and advanced genome manipulation methods. In cyanobacteria in general, but especially in Thermosynechococcus, it is more difficult to achieve specific integration due to less effective homologous recombination machinery (unpublished data) and attempts to develop protocols of obtaining miniploid cells are not as successful as those employed for mesophilic model strains (Riaz et al 2021(Riaz et al , 2022. Moreover, in the absence of established genome editing tools based on CRISPR/Cas9 methodology, presumably due to the high toxicity of nucleases (unpublished data) and potential thermal instability of mesophilic proteins, specific genome engineering of thermophilic cyanobacteria remains a tedious task.…”
Section: Discussionmentioning
confidence: 99%
“…Even those relatively simple organisms lack reliable genetic modules and advanced genome manipulation methods. In cyanobacteria in general, but especially in Thermosynechococcus, it is more difficult to achieve specific integration due to less effective homologous recombination machinery (unpublished data) and attempts to develop protocols of obtaining miniploid cells are not as successful as those employed for mesophilic model strains (Riaz et al 2021(Riaz et al , 2022. Moreover, in the absence of established genome editing tools based on CRISPR/Cas9 methodology, presumably due to the high toxicity of nucleases (unpublished data) and potential thermal instability of mesophilic proteins, specific genome engineering of thermophilic cyanobacteria remains a tedious task.…”
Section: Discussionmentioning
confidence: 99%
“…However, this was accompanied by a 100-fold drop in transformation efficiency [ 115 ]. Analogously, Riaz et al found out that the reduction of phosphate and agar concentration in the growth medium and high temperature are key parameters for reducing polyploidy and accelerating segregation process [ 116 ].…”
Section: Current Methods For Dna Transfer Into Cyanobacteriamentioning
confidence: 99%
“…The cscB containing plasmid (pLJD31) was transformed into E542 through the conjugation via E. coli HB101 harboring pRL443 and pRL623 (Thiel and Peter Wolk, 1987) and E. coli DH5α carrying the pLJD31 plasmids, respectively. Meanwhile, the pLJD32 was transformed into PCC7942 using the recently optimized protocol (Riaz et al, 2022).…”
Section: Strainsmentioning
confidence: 99%